Ingesting the future: Navigating the perils of Nano-liquid urea A case study & Review of Literature - Roy, Deep; Das, Sunita; Pradhan, Monisha; Tyagi, Yogesh; Tandon, S K (Journal of Forensic Medicine and Toxicology, 2025)
This case study aims to present the first documented suicide attempt involving the ingestion of nano-liquid urea, a nano technology-based fertilizer recently introduced in Indian agriculture. This study examines the clinical aspects including signs, symptoms, laboratory investigations, and treatment, while simultaneously exploring the underlying psychosocial aspects. By doing so, our goal is to illuminate the intersection between technological advancement, human vulnerability, and the responsibilities that come with scientific innovation.